The Probe Team [episode no. 307] - Patinio, Joe (Quezon City Probe Productions, 1994)
Here they go again is about the Mt. Pinatubo lahar victims in their resettlement area in Tarlac. Chorela is discussed in the second part. Signature Art is an interview with Joe Patinio.
Here they go again (17 min.) -- Call'er cholera (13 min.) -- Signature Art (10 min.)
Reporting, Marga Ortegas, Luchi Cruz Valdes.
Keywords: Disaster victims -- Pinatubo, Mount (Philippines).; Cholera -- Philippines